1992
DOI: 10.1002/bies.950140810
|View full text |Cite
|
Sign up to set email alerts
|

Is calpain activity regulated by membranes and autolysis or by calcium and calpastatin?

Abstract: Although the Ca(2+)-dependent proteinase (calpain) system has been found in every vertebrate cell that has been examined for its presence and has been detected in Drosophila and parasites, the physiological function(s) of this system remains unclear. Calpain activity has been associated with cleavages that alter regulation of various enzyme activities, with remodeling or disassembly of the cell cytoskeleton, and with cleavages of hormone receptors. The mechanism regulating activity of the calpain system in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
139
1
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 56 publications
3
139
1
3
Order By: Relevance
“…The calpains, a large family of Ca 2+ -dependent cysteine peptidases, also require significantly higher levels of Ca 2+ for activation in vitro than have been measured intracellularly. It has been postulated that association with cofactors or phospholipids, proteolysis, or a combination of these factors, can lower the Ca 2+ -activation threshold for calpains [20]. Similar mechanisms might exist for MCA2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…The calpains, a large family of Ca 2+ -dependent cysteine peptidases, also require significantly higher levels of Ca 2+ for activation in vitro than have been measured intracellularly. It has been postulated that association with cofactors or phospholipids, proteolysis, or a combination of these factors, can lower the Ca 2+ -activation threshold for calpains [20]. Similar mechanisms might exist for MCA2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…The two major, ubiquitously distributed isoforms calpain I and calpain II are composed of unique 80-kDa subunits and common 30-kDa subunits, and have been classically distinguished because in vitro activation of calpain I requires a lower calcium concentration than calpain II (Mellgren, 1987;Suzuki et al, 1987;Goll et al, 1992). Calpains land II, as well as their endogenous inhibitor calpastatin, are present in neurons; however, their patterns of expression in both mRNA and protein levels differ depending on locations and/or cell types (Hamakubo et al, 1986;Perlmutter et al, 1990;Goto et a!., 1994;Li et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The protease m-calpain (for review of calpain, see Goll et al, 1992) has been implicated as the major causative agent for many of the proteolytic changes that occur as meat is aged. Researchers using enzyme caseinolytic activity, SDS-PAGE, and microscopy of digested myofibrils have shown that m-calpain retains at least partial activity under PM conditions of low pH and temperature (Koohmaraie et al, 1986(Koohmaraie et al, , 1987.…”
Section: Introductionmentioning
confidence: 99%